2014
DOI: 10.1007/s10646-014-1392-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased temperatures on Gammarus fossarum under the influence of copper sulphate

Abstract: The specialised fauna of freshwater springs will have to cope with a possible temperature rise owing to Global Change. It is affected additionally by contamination of the water with xenobiotics from human activities in the surrounding landscape. We assessed the combined effects of temperature increase and exposure to toxins in laboratory experiments by using copper sulphate as a model substance and Gammarus fossarum Koch, 1835, as the model organism. This amphipod is a common representative of the European spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Considering that the thermal optimum for G. fossarum is approximately 11.5°C (P€ ockl & Humpesch, 1990), with potential variations depending on the geographical origin of the population (Foucreau et al, 2013b(Foucreau et al, , 2014, it is not surprising that a temperature of 18°C would induce a nonlethal thermal stress, with consequences on food consumption. Similarly, Schmidlin et al (2015b) observed a slightly reduced feeding activity of G. fossarum above 16°C, while that of males Dikerogammarus villosus decreased between 20 and 25°C (Pellan et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Considering that the thermal optimum for G. fossarum is approximately 11.5°C (P€ ockl & Humpesch, 1990), with potential variations depending on the geographical origin of the population (Foucreau et al, 2013b(Foucreau et al, , 2014, it is not surprising that a temperature of 18°C would induce a nonlethal thermal stress, with consequences on food consumption. Similarly, Schmidlin et al (2015b) observed a slightly reduced feeding activity of G. fossarum above 16°C, while that of males Dikerogammarus villosus decreased between 20 and 25°C (Pellan et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, Schmidlin et al . () observed a slightly reduced feeding activity of G. fossarum above 16 °C, while that of males Dikerogammarus villosus decreased between 20 and 25 °C (Pellan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that organisms living under environmental conditions that are near to their tolerance limits are often less resistant to additional stressors, such as exposure to pollutants (Heugens, 2003). In previous experiments with fluctuating temperatures, we concluded that a water temperature of 12-14 • C was probably more optimal for G. fossarum (Schmidlin et al, 2014). The gammarids in the spring are exposed to 10 • C throughout the year and although the gammarids in the laboratory were also exposed to 10 • C, they were not subjected to additional stressors when compared to those in the spring.…”
Section: Laboratory Versus Field Experimentsmentioning
confidence: 85%
“…The range of 0.4-6.4 mg Cu/L was chosen loosely on previously conducted LC 50 -tests (see Schmidlin et al, 2014). We started off with a ten times higher concentration than for the LC 50 -tests and then always doubled the concentrations in order to obtain a concentration range suitable for testing.…”
Section: Choice Of Copper Concentration For Leaf Disc Exposurementioning
confidence: 99%
“…Finally, a toxicity test with G. roeseli was conducted to validate the suitability of miniature circulatory system for ecotoxicological investigations. Copper as Cu 2þ was used as the test substance, because data on copper toxicity to different Gammarus species with variable test durations already exist [35,36], allowing a qualitative assessment of the results obtained through the novel exposure system by comparing the LC50 values (concentration that causes 50% mortality).…”
Section: Introductionmentioning
confidence: 99%